2016
DOI: 10.1007/s00345-016-1871-x
|View full text |Cite
|
Sign up to set email alerts
|

HER2 overexpression is associated with worse outcomes in patients with upper tract urothelial carcinoma (UTUC)

Abstract: Approximately, one-third of UTUC patients overexpressed HER2. HER2 overexpression was associated with features of clinically and biologically aggressive disease as well as prognosis. HER2 may represent a good marker for therapeutic risk stratification and potentially a target for therapy in some UTUC tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…In the largest single-center HER-2 study in UTUC patients ( 32 ), Sasaki et al investigated HER-2 status in 171 UTUC patients who underwent RNU and found that overexpression and amplification of HER-2 was associated with early bladder cancer recurrence. These findings were validated by a large multicenter retrospective study of 732 patients ( 33 ), in which Soria and colleagues found that HER-2 was overexpressed in 35.6% of patients and linked to pathological characteristics, such as more advanced T stage, presence of lymph node metastasis, high-grade tumor, tumor necrosis, and lympho-vascular invasion. By multivariable analysis, HER-2 overexpression remained associated with disease recurrence and overall and cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 82%
“…In the largest single-center HER-2 study in UTUC patients ( 32 ), Sasaki et al investigated HER-2 status in 171 UTUC patients who underwent RNU and found that overexpression and amplification of HER-2 was associated with early bladder cancer recurrence. These findings were validated by a large multicenter retrospective study of 732 patients ( 33 ), in which Soria and colleagues found that HER-2 was overexpressed in 35.6% of patients and linked to pathological characteristics, such as more advanced T stage, presence of lymph node metastasis, high-grade tumor, tumor necrosis, and lympho-vascular invasion. By multivariable analysis, HER-2 overexpression remained associated with disease recurrence and overall and cancer-specific mortality.…”
Section: Introductionmentioning
confidence: 82%
“…A higher incidence rate of UTUC was reported in Asians than western countries, generally about 20-36% in most Asian cohorts with mUC (24).Two phase II trials of two PD-1 antibodies originated in China, toripalimab and tislelizumab, for the treatment of mUC after progression of platinum chemotherapy reported to have 47.2% (25) and 47.0% (26) of mUTUC, respectively, similar to our patient population. 9.4%-41.2% of UBC patients (7,27) and 18.1-35.8% of UTUC (28,29) patients were reported to overexpressed HER2. We did not observe obvious difference in the HER2 expression rate between UTUC and UBC patients in our study (44.1% vs 49.2% in the screened patients).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous prognostic molecular biomarkers in UTUC have been described ( Table 5 ). These biomarkers are implicated in every steps of tumorigenesis and progression from cell-cycle regulation [mTOR pathway ( 99 )] to cell-proliferation [HER2 ( 91 ), Ki-67 ( 95 - 97 , 113 ), BCAT1 ( 83 ), CDCA5 ( 84 )] and apoptosis [p53 ( 100 )]. Unfortunately, most of them have been described in single-institution cohorts and very few factors beneficiated from external validation.…”
Section: Evidence Synthesismentioning
confidence: 99%